2002
DOI: 10.1097/00004872-200202000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Irbesartan lowers superoxide levels and increases nitric oxide bioavailability in blood vessels from spontaneously hypertensive stroke-prone rats

Abstract: These studies support the hypothesis that AT1 receptor blockade has beneficial effects on superoxide production and nitric oxide bioavailability above that of other classes of antihypertensive agents. Reduced expression of components of the NAD(P)H oxidase may contribute to these effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
1
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(34 citation statements)
references
References 29 publications
2
30
1
1
Order By: Relevance
“…We have previously validated this method to calculate NO bioavailability in rat carotid arteries infused with genes encoding NO synthase and superoxide dismutase 5,22 and to investigate effects of antihypertensive drugs on NO bioavailability in vivo and in vitro. 23 When expressed in this format, the apocynin-induced increases in NO bioavailability were greater than those observed in any of the previous studies and were greater that that achieved by scavenging of O 2 Ϫ with PEGSOD in the present study. When arteries from the 3-month-old SHRSP and WKY were compared, no differences were observed in NAD(P)Hstimulated O 2 Ϫ generation, apocynin inhibition of this O 2 Ϫ generation, or levels of expression of mRNA for the membrane-integrated components of the NAD(P)H oxidase system.…”
Section: Discussioncontrasting
confidence: 59%
“…We have previously validated this method to calculate NO bioavailability in rat carotid arteries infused with genes encoding NO synthase and superoxide dismutase 5,22 and to investigate effects of antihypertensive drugs on NO bioavailability in vivo and in vitro. 23 When expressed in this format, the apocynin-induced increases in NO bioavailability were greater than those observed in any of the previous studies and were greater that that achieved by scavenging of O 2 Ϫ with PEGSOD in the present study. When arteries from the 3-month-old SHRSP and WKY were compared, no differences were observed in NAD(P)Hstimulated O 2 Ϫ generation, apocynin inhibition of this O 2 Ϫ generation, or levels of expression of mRNA for the membrane-integrated components of the NAD(P)H oxidase system.…”
Section: Discussioncontrasting
confidence: 59%
“…A recent study in spontaneously hypertensive rats supports this observation (31). We used norepinephrine as a control because it results in a reduction of FBF similar to that by angiotensin II, thereby controlling for the nonspecific effects of decreased FBF.…”
Section: Fig 2 (A) Response Of Fbf To Acetylcholine (Ach) Before (Wmentioning
confidence: 64%
“…Endothelial vasodilator function is influenced by a balance between the production of NO and superoxide anions (6,7,29). Recent studies in animals suggest that an imbalance occurs due to decreased bioavailability of NO from either decreased production of NO by endothelial cells or increased degradation of NO by oxygen-derived free radicals (5,(30)(31)(32). NO has a very short half-life (from 0.5 to 5 s) and is rapidly broken down by superoxide anions under physiologic conditions (33).…”
Section: Discussionmentioning
confidence: 99%
“…7,8,15 Endothelial function is directly affected by nitric oxide bioavailability, and its dysfunction is associated with oxidative stress induced by angiotensin II. 16,17 In an earlier report, although losartan and trichlormethiazide at equivalent hypotensive doses were administered for 2 weeks in SHR-SP, the mRNA levels of NADPH oxidase subunits and oxidative stress were significantly reduced by losartan, but not by trichlormethiazide. 18 Pu et al 19 showed that valsartan and hydralazine showed the same hypotensive effect in SHR-SP, but that valsartan, but not hydralazine, reduced endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 93%